(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud computing provides a simplest way of data sharing, it provides various benefits to the users. But directly outsourcing the shared data to the cloud server will bring security issues as the data may contain valuable information. Hence, it is necessary to place cryptographically enhanced access control on the shared data, named Identity-based encryption to build a practical data sharing system. when some user’s authorization is expired, there should be a mechanism that can remove him/her from the system. Consequently, the revoked user cannot access both the previously and subsequently shared data. Thus, we propose a notion called revocable-storage identity-based encryption (RS-IBE), which introducing the functionalities of user revocation and cipher text update simultaneously.